Evaluation on e-marketing exposure practice to minimize the customers' online shopping purchase regret - Arlina Nurbaity Lubis; Prihatin Lumbanraja; Beby Kendida Hasibuan (Cogent Business & Management, 2022)
As many of recent study showed that e-marketing activities lead into higher marketing performance such as sales, we believe that e-marketing should be evaluated in terms of its negative impact on marketing practices. This study aimed to evaluate e-marketing exposure and its impact on consumer behavior. Although we believed that marketing could lead a better purchase experience and sales, this study proposed that marketing could also lead into regretful experience to customers. In order to evaluate the regret model in online shopping activities, we proposed a behavioral model based on e-marketing exposure. In total, 400 participants were used in this study. Totally, 363 had regretful experience on online market and used in this study indicating 90.75% data used in this study. Data were collected through questionnaires given to online consumer. Data were analyzed through SEM-PLS as we employ 4-point forced likert scale, which lead to non-parametric analysis. As a result, we found that the excessive marketing exposure ultimately led to higher regret level to the customers. It is true that e-marketing exposure led to desirable behavior such as more rational at evaluating price and shaping a good image and perception toward the products; however, it also led to higher chance for impulsive buying behavior. This behavior led to purchasing regret. As we want to avoid regret as many as possible due to sustainable purchase and growth in the future, we must control e-marketing exposure so that it will not lead to regret on customers.
Keywords: 650; E-marketing exposure; impulsive buying; online shopping behavior; post-purchase regret